Estimation of Arsenic(III) by Adsorption and Filtration from Wastewater of Kanti Thermal Power, Muzaffarpur (India) - Kumari, Kalpna (Asian Journal of Chemistry, 2010)
Adsorption process of As3+ from effluent of Kanti thermal power was found to be dependent on concentration of adsorbent and adsorbate, pH of solution, temperature, particle size of adsorbent and agitation speed of the system. It is observed that favourable conditions for arsenic removal are: equilibrium time of 50 min, pH of 7.5 and agitation speed of 190 rpm. The removal of As3+ has been found in the range of 87-95 %.